Conceal or reveal? Patterns of self-disclosure of long-term conditions at work by health professionals in a large regional Australian health service. Issue 5 (26th September 2019) - Lindsay, David; Brennan, Daryl; Lindsay, Daniel; Holmes, Colin; Smyth, Wendy
Abstract : Purpose: The purpose of this paper is to describe the patterns of self-disclosure of long-term conditions at work by health professionals in a large regional health service. Recent research by the authors has reported on the self-reported long-term conditions of nursing, medical and allied health staff within a large regional hospital and health service in North Queensland, Australia. Data regarding self-disclosure of health information were gathered during those two previous studies, but has yet to be reported. This current study thus offers the opportunity to explore and describe patterns of self-disclosure by a multi-disciplinary cohort of health professionals within that regional health service. Design/methodology/approach: This current study was a component of two larger studies, reported elsewhere, which explored long-term conditions among health professional staff at a large regional health service in North Queensland, Australia. A cross-sectional survey design was used. Findings: Decision-making associated with self-disclosure of long-term conditions by health professional staff in the workplace is multifactorial, and affected by considerations of age, gender, workplace circumstances and nature of the health condition. It also differs according to professional grouping. The medical profession were less likely than nurses and allied health workers to disclose to their work colleagues. Respondents with a mental health condition were more cautious and selective in their disclosures, and alone in being more likely to disclose to their supervisor than to colleagues; they were also most likely to value the sympathy and understanding of their colleagues and managers. Research limitations/implications: This study was conducted across only one large regional health service; a fuller picture of patterns of self-disclosure of long-term conditions by health professional staff would be gained by expanding the number of sites to include metropolitan hospitals, smaller rural or remote health services and non-hospital settings. Practical implications: Healthcare organizations need to develop support strategies and communication processes so that staff with one or more long-term condition, particularly those that have associated stigma, are empowered to disclose information to line managers and colleagues without fear of discrimination, ostracism, incivility or bullying. Originality/value: There is a paucity of evidence about self-disclosure of long-term conditions by health professionals and this study therefore makes an important contribution to the extant literature. The findings raise important questions about the culture and dynamics of health care organizations in respect to the patterns of self-disclosure of health professional staff.